The effect of diet therapy on the anthropometric and metabolic parameters in women with infertility and obesity - N. V. Artymuk; O. A. Tachkova; N. A. Sukhova (Акушерство, гинекология и репродукция, 2020)
Aim: to monitor the anthropometric, hormonal and metabolic parameters in women of reproductive age with infertility and grade I gluteofemoral obesity during treatment with a balanced hypocaloric diet.Materials and methods. The study included 23 infertile women of reproductive age. All patients were prescribed a balanced, low-calorie diet (1200 kcal/day), exercise, and behavioral therapy. The anthropometric, metabolic and hormonal parameters were determined before and 12 months after the treatment. We measured the levels of leptin, total cholesterol, triglycerides, triglycerides, high-density and low-density lipoprotein cholesterol (HDL cholesterol and LDL cholesterol), fasting glycose. Following the measurements, the atherogenic and insulin resistance indices were calculated. In addition, the plasma concentrations of luteinizing hormone, follicle-stimulating hormone, prolactin, estrone, estradiol, testosterone, progesterone, and immunoreactive insulin were measured.Results. Twenty patients completed the study. A decrease in body weight (by average of 10.58 ± 5.70 kg) was found in 87 % of patients; in parallel, the body mass index decreased from 32.53 ± 1.40 to 28.55 ± 2.50 kg/m2 (p < 0.001). The decrease in body weight was accompanied by a statistically significant decrease in the levels of leptin (p < 0.001), estrone (p = 0.049), estradiol (p = 0.032), total cholesterol (p < 0.001), triglycerides (p = 0.004), LDL cholesterol (p = 0.001), fasting glycose (p < 0.001), insulin resistance index (p = 0.002), atherogenic index (p < 0.001) and an increase in the level of progesterone (p = 0.030). The ovulatory menstrual cycle was restored in all women (p = 0.007); within one year, wanted pregnancy occurred in 1 woman.Conclusion. The use of a low-calorie diet for 12 months in infertile women with grade I gluteofemoral obesity leads to normalization of metabolic parameters, weight loss and, the restoration of the ovulatory menstrual cycle in 100 % of cases.